A review of Directed Reading Thinking Activity (DRTA) strategy in teaching reading comprehension - Melisa Safitri; Saiful Marhaban; Nira Erdiana (Universitas Syiah Kuala, 2022)
The purpose of this study is to ascertain whether the Directed Reading Thinking Activity (DRTA) technique enhances students' reading comprehension. The data used in this study were gathered using a library research methodology. Some of the literature sources used in this study included books and journals. The steps involved in the data analysis technique are data identification from pertinent literature sources, location identification, data acquisition, data evaluation, and data incorporation into the research presentation. The findings of this study demonstrate that students' reading comprehension abilities increased after receiving treatment with the DRTA technique employing its three fundamental steps (Predicting, Reading, and Proving). The students' test results supported the findings, and the application of the DRTA technique can assist pupils in resolving their reading difficulties. In conclusion, the DRTA approach is regarded as a successful teaching method that helps raise students' reading comprehension abilities.